Auxin-BR Interaction Regulates Plant Growth and Development - Tian, Huiyu; Lv, Bingsheng; Ding, Tingting; Bai, Mingyi; Ding, Zhaojun (Frontiers in Plant Science, 2018)
Plants develop a high flexibility to alter growth, development and metabolism to adapt to the ever-changing environments. Multiple signaling pathways are involved in these processes and the molecular pathways to transduce various developmental signals are not linear but are interconnected by a complex network and even feedback mutually to achieve the final outcome. This review will focus on two important plant hormones, auxin and brassinosteroid (BR), based on the most recent progresses about these two hormone regulated plant growth and development in Arabidopsis, and highlight the cross-talks between these two phytohormones.